Cybersecurity of Public Sector Institutions - Gaie, Christophe; Karpiuk, Mirosław; Strizzolo, Nicola (PRAWO i WIĘŹ, 2025)
In the information society, the public sector must anticipate needs related to the ever-present use of cyberspace for providing services. On the one hand, new technologies facilitate and streamline the fulfillment of public tasks, and on the other hand, they pose threats that might produce far-reaching consequences. This means that public entities are obliged to apply solutions adequate to potential threats. As information and communication technology (ICT) systems being used by public sector institutions should operate uninterruptedly, it is necessary to implement measures to ensure such systems’ resilience to cyberattacks.  Artificial intelligence (AI) might prove helpful for ensuring cybersecurity. However, this technology should be used with caution to prevent damage to the public sector resulting from its improper use.The research methods used in this paper include both the law theory method and the doctrinal legal research method. These methods were applied to analyze the literature on the subject and legal texts from the perspective of cybersecurity in the public sector. The paper also emphasizes the necessity of considering evolving cybersecurity frameworks that account for the global nature of cyberthreats, as well as the unique challenges faced by public institutions in balancing efficiency with security needs.